Validation study on a new semi-empirical method for the prediction of added resistance in waves of arbitrary heading in analyzing ship speed trial results. (15th November 2021) - Wang, Jinbao; Bielicki, Sebastian; Kluwe, Florian; Orihara, Hideo; Xin, Gongzheng; Kume, Kenichi; Oh, Semyun; Liu, Shukui; Feng, Peiyuan
Abstract: This paper describes an open and extensive validation study carried out by the Specialist Committee on Ships in Operation at Sea (SOS) of the International Towing Tank Conference (ITTC) on the newly developed SHOPERA-NTUA-NTU-MARIC (SNNM) wave-added resistance prediction method. The SNNM method aims at a simple, fast and transparent determination of the added resistance in regular waves of arbitrary encounter directions, even when the hull geometry is not available. Prior to the validation study, a series of acceptance criteria for the new method were specified by the committee. Contributions of 1, 477 added resistance experimental data samples from 8 institutions were collected, analyzed and cross-checked with satisfactory outcome, which finally led to the inclusion of the new method into the ITTC recommended sea trial procedure as an important progress. Some aspects of concerns are discussed in detail and further work in the future is recommended. Highlights: Latest and most remarkable progress of ITTC recommended sea trial procedure for analyzing the wave effect in arbitrary direction. Establishment of a high-quality experimental added resistance database about 1500 points for open validation study. Validation study is carried out strictly following agreed procedure by all ITTC-SOS committee members. The performance of new method is much better than agreed as acceptance criteria. The behavior of added resistance in relatively short waves is elaborated.